Pre-service Accounting education teachers’ experiences of active learning through group work at a university in South Africa - Ngwenya, J. C.; Arek-Bawa, O. O. (South African Journal of Higher Education, 2021)
This article explores pre-service teachers’ experiences of active learning through group work in Accounting Education. The study employed a qualitative case study. Data were obtained through semi-structured individual and focus group interviews from forty purposively selected pre-service Accounting teachers. Reflective journals were used to supplement the interviews. Thematic data analysis was used to analyse pre-service teachers’ experiences. What emerged from the findings is that participants acknowledged the role of group work in assisting their learning by creating a supportive social environment that allows opportunities for active learning. The majority of the pre-service teachers, including those who are usually shy and less assertive, were inspired to express themselves in a more relaxed manner without being ridiculed. Engagement in small group work led to positive interdependence and interaction while developing interpersonal and social skills. Diversity in members created spaces for students to create diverse analytical approaches to resolving Accounting problems.